Faktor yang Mempengaruhi Peluang Keputusan Pembelian Kentucky Fried Chicken ( KFC ) Cabang Banjarbaru di Kota Banjarbaru - Mariana Pebriana Simanjuntak; Nuri Dewi Yanti; Nina Budiwati (Universitas Lambung Mangkurat, 2014)
The consumption is the largest contribution of economic growth . Currently , economic progress has changed the life style and consumption pattern . The demand of high quality food but fast served with affordable price has increased. As a result, the growth of fast food business increases rapidly. This increased demand is an opportunity of fast food business. The study is purposed to: (1) analyze the factor influenced the decision probability to purchase the KFC's products; and (2) to excavate the consumer decision process to purchase. The population the resident of four administrative villages (kelurahan) which has highest population density in Kota Banjarbaru, that are: Komet, Sungai Ulin, Kemuning and Loktabat Selatan. The disproporsional random sampling was applied to select 25 respondents fro m each village, hence 100 respondents were involved in this study. Based on the logistic regression, it is estimated that income and age significantly influence the probability to purchase. The information gathered from self-seeking and is mass media also influence the probability. The decision process and time to purchase are highly depending on the situation. The 71.67% of respondents are satisfied with the decision and all respondents repurchase the product during the last 3 months.